Banned Expression - Wangdue, Sonam (Norway, 2014)
Tibet is closed to the outside world. Basic human rights, like freedom of speech and expression, are brutally supressed. Still Tibetans defy China’s repressive policies and fight for their country, culture and identity. Tibetan writers and artists fearlessly continue to challenge China’s policies. In the meantime they are being censored, arrested, tortured and imprisoned.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films